Correlation of Natural Law Theory with Sharia Economic Law Studies - Salfin Abdul Rahman Al’auf; Hasan Bisri; Ayi Yunus Rusyana (Yayasan Mentari Madani, 2023)
In the study of a science there are many views related to the science because in human thought has its own truth based on what they believe and can be used as a reference to the foundation of science. Inseparable from the definition of legal science or legal theory, many philosophies express their opinions about legal theory taken from various scholarly figures from various countries with their own opinions. With this opinion, it is very cool to study from these various definitions to become the basis of science and also the theoretical basis for the study. In this research method, the author uses qualitative methods that are separated from texts, books, images, and others which are not numerical targets, where the results of the research are described in the form of writing that explains something. In conclusion, natural law is a law that applies to all nations because natural law exists everywhere based on human instinct and not because of announcement or promulgation by man. Andrew Altman examines